Cryptocurrencies in India: Investor Sentiments and Economic Impact - Sachin Chavan, Manisha Khaladkar, Parikshit Mahankal, Anil Poman, Apoorva Sharma (European Economic Letters (EEL), 2024)
Cryptocurrencies, digital or virtual currencies using cryptography for secure transactions, have gained significant attention in recent years, particularly in India. The impact of cryptocurrencies on investors and the Indian economy is a topic of growing interest. As a new technology, cryptocurrency has attracted increasing attention due to its potential as an alternative to fiat currencies. This paper presents an overview of the current state of cryptocurrencies in India. Key industry players believe that India, as an emerging tech and economic power, will become a key player in crypto and blockchain adoption. The use of Bitcoin and Ethereum could help strengthen monetary policy, attract international capital, create more job opportunities, and retain tech talent to accelerate technological development, driving the nation towards becoming a global powerhouse. This study provides an opportunity to develop analytical skills, technical skills, and exposure to the digital currency revolution. The research method used was a survey through a questionnaire